Defects of Nutrient Signaling and Autophagy in Neurodegeneration - Ondaro, Jon; Hernandez-Eguiazu, Haizea; Garciandia-Arcelus, Maddi; Loera-Valencia, Raúl; Rodriguez-Gómez, Laura; Jiménez-Zúñiga, Andrés; Goikolea, Julen; Rodriguez-Rodriguez, Patricia; Ruiz-Martinez, Javier; Moreno, Fermín; Lopez de Munain, Adolfo; Holt, Ian James; et al. (Frontiers in Cell and Developmental Biology, 2022)
Neurons are post-mitotic cells that allocate huge amounts of energy to the synthesis of new organelles and molecules, the neurotransmission and the defense against oxidative stress. In neurons, autophagy is not only important to make up for the deficiency of organelle renewal that takes place during cell division in mitotic cells, but it is also essential to balancing nutritional needs through the mobilization of internal energy stores. A delicate crosstalk between the pathways that sense nutritional status of the cell and the autophagic processes to recycle organelles and macronutrients is fundamental to guarantee the proper functioning of the neuron in times of energy scarcity. This review provides a detailed overview of the pathways and processes involved in the balance of cellular energy mediated by the autophagy, which when defective precipitate the neurodegenerative cascade of Parkinson’s disease, frontotemporal dementia, amyotrophic lateral sclerosis or Alzheimer’s disease.